Association of PLGA Microspheres to Carrier Pellets by Fluid Bed Coating: A Novel Approach towards Improving the Flowability of Microparticles. (2nd July 2018) - Beringhs, André O'Reilly; Fonseca, Aline Benedita dos Santos; De Campos, Angela Machado; Sonaglio, Diva
Abstract : Micro- and nanoparticles have been vastly studied due to their biopharmaceutical advantages. However, these particles generally display very weak packing and poor mechanical properties. Hereby, a new methodology is proposed to associate poorly flowing particles to macrostructures targeting the improvement of flowability and redispersibility of the particles. Cecropia glaziovii -loaded PLGA microspheres (4.59 ± 0.04 μ m) were associated with carrier pellets by film coating in a top-spray fluid bed equipment. Optimal conditions were determined employing a IV-Optimal factorial design and RGB image analysis as 1% (w/v) Kollicoat® Protect as coating polymer (2:1 weight ratio of coating suspension to carrier pellets), containing 5 mg/mL microspheres (loading of 28.07 ± 1.01 mg/g). The method led to an improvement of the overall flowability. No relevant molecular interactions between PLGA microspheres and polymers were found. Microspheres detached rapidly from the surface of the pellets, without agglomeration, when exposed to hydrodynamic forces. In vitro release profiles, prior to and after fluid bed coating, showed no relevant changes in drug release rate and extent. The methodology developed is suitable for further applications when an improvement on the flow properties and redispersibility of the product is desired. We showed an easy-to-implement methodology that can be executed without significant increase in costs.